2019
DOI: 10.3390/cancers11111782
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Curability of Cancers: More Efforts for Novel Therapeutic Options Are Needed

Abstract: Cancer remains a major cause of death globally. Given its relapsing and fatal features, curing cancer seems to be something hardly possible for the majority of patients. In view of the development in cancer therapies, this article summarizes currently available cancer therapeutics and cure potential by cancer type and stage at diagnosis, based on literature and database reviews. Currently common cancer therapeutics include surgery, chemotherapy, radiotherapy, targeted therapy, and immunotherapy. However, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 282 publications
(229 reference statements)
1
52
1
1
Order By: Relevance
“…However, nearly radical effect was paradoxically discovered in hepatic micro-HCCs [24], which is against earlier consensus that normally tumors smaller than 5 mm lack their own vasculature and are nourished by the blood diffused from their host organs [71]. This counterintuitive observation was reproduced in a rodent model with secondary liver malignancy [72]. Further studies comparing conventional and immunohistochemical (IHC) staining indicated that those micro-cancers looked avascular on H&E stained slide, but CD34 staining revealed an intratumoral network of endothelium, suggesting that such an endothelial network could be 1) functional and vital for supplying nutrients to cancer cells, and 2) vulnerable to VDA attack resulting in nearly complete tumor necrosis [72].…”
Section: Distinct Volume-efficacy Relation Between Micro-hccs and Macmentioning
confidence: 88%
See 4 more Smart Citations
“…However, nearly radical effect was paradoxically discovered in hepatic micro-HCCs [24], which is against earlier consensus that normally tumors smaller than 5 mm lack their own vasculature and are nourished by the blood diffused from their host organs [71]. This counterintuitive observation was reproduced in a rodent model with secondary liver malignancy [72]. Further studies comparing conventional and immunohistochemical (IHC) staining indicated that those micro-cancers looked avascular on H&E stained slide, but CD34 staining revealed an intratumoral network of endothelium, suggesting that such an endothelial network could be 1) functional and vital for supplying nutrients to cancer cells, and 2) vulnerable to VDA attack resulting in nearly complete tumor necrosis [72].…”
Section: Distinct Volume-efficacy Relation Between Micro-hccs and Macmentioning
confidence: 88%
“…This counterintuitive observation was reproduced in a rodent model with secondary liver malignancy [72]. Further studies comparing conventional and immunohistochemical (IHC) staining indicated that those micro-cancers looked avascular on H&E stained slide, but CD34 staining revealed an intratumoral network of endothelium, suggesting that such an endothelial network could be 1) functional and vital for supplying nutrients to cancer cells, and 2) vulnerable to VDA attack resulting in nearly complete tumor necrosis [72].…”
Section: Distinct Volume-efficacy Relation Between Micro-hccs and Macmentioning
confidence: 99%
See 3 more Smart Citations